Pengaruh Lingkungan Kerja Hibrida terhadap Kinerja Karyawan di Era Digital: Sebuah Analisis Bibliometrik - Bambang Libriantono; Sumardi; Slamet Riyanto (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to: (1) analyze the development of research related to hybrid work environments and employee performance in the digital era, (2) identify trends, collaboration patterns, and dominant topics in the scientific literature, and (3) evaluate the impact of hybrid work environments on employee performance based on bibliometric analysis. The research method employed is a quantitative approach using bibliometric analysis, with publication data sourced from Google Scholar within the 2019–2025 period. Data collection was conducted using the Publish or Perish (PoP) application, resulting in 100 selected articles. The data were analyzed using VOSviewer software to map co-authorship, co-occurrence, and citation networks. The results indicate that research on hybrid work environments has experienced significant growth since the COVID-19 pandemic, with primary focuses on productivity, work flexibility, and employee well-being. Hybrid work environments are found to have a positive impact on employee performance, particularly through increased flexibility and job satisfaction, although challenges remain in communication and team coordination. This study recommends that organizations optimize hybrid work management strategies by leveraging digital technologies, enhancing communication, and implementing adaptive work policies to sustainably improve employee performance.